Детская энциклопедия: [в 10 томах, в 20 книгах : перевод] (Открытие мира юношеством, 1995)
Экземпляры: аб. (1996) / Инвентарный номер: 38654 / Цена: / Сис.шифр: 92 / Авт.знак: Д 38 / ГРНТИ: 00 / ББК: 92